How do you evaluate e^( ( 11 pi)/6 i) - e^( ( pi)/8 i) using trigonometric functions?

1 Answer
Apr 8, 2016

- 0.188 + 0.355i

Explanation:

According to Euler's formula,

e^(ix) = cosx + isinx.

If we substitute the two values, beginning with (11pi)/6,

cos((11pi)/6) + isin((11pi)/6) = cos330 + isin330
= - 0.991 - 0.132i

x = pi/8
cos(pi/8) + isin(pi/8) = cos22.5 + isin22.5
= - 0.873 - 0.487i

Putting the two together,

e^((11pi)/6i) - e^((pi/8)i) = - 0.991 + 0.873 - 0.132i + 0.487i
= - 0.118 + 0.355i